BIMBINGAN TEKNIS PENCATATAN AKUNTANSI KOPERASI PADA KOPERASI DESA SELEBUNG MADANI - Syarifah Massuki Fitri; Syukri Syukri; Suandi Suandi (LPPM Institut Pendidikan Nusantara Global, 2025)
This community service activity aims to improve the understanding of cooperative administrators in Selebung Madani Village regarding accounting records and the preparation of financial reports according to standards. The main problem faced is the low understanding of accounting records among administrators, especially regarding the journaling process, cooperative accounting flows, and the use of financial reports as a basis for decision-making. This activity uses an interactive lecture-based training approach and discussions, with 20 cooperative administrators and members participating in the Coaching Clinic program. Data collection instruments include observations during the training and participant responses in the discussion sessions to determine improvements in understanding. The results of the activity showed an increase in participants' knowledge of the basic concepts of cooperatives, accounting standards, and financial recording practices, from cash inflows and outflows to the preparation of financial reports. Participants were able to understand the differences between manual and digital recording and demonstrated high enthusiasm through questions and discussions. Their understanding of financial position, financial performance, and the function of financial reports also improved after the material was presented. This activity concluded that technical accounting training was effective in strengthening the competency of cooperative administrators, particularly in improving accountability and the quality of financial governance. This community service provided a practical contribution to the capacity development of village cooperatives and served as a basis for the development of sustainable training programs relevant to the administrators' needs.